Search for lepton-number violating B+→X−ℓ+ℓ'+ decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We report on a search for eleven lepton-number violating processes B+→X−ℓ+ℓ'+ with X−=K−, π−, ρ−, K*−, or D− and ℓ+/ℓ'+=e+ or μ+, using a sample of 471±3 million B¯B events collected with the BABAR detector at the PEP-II e+e− collider at the SLAC National Accelerator Laboratory. We find no evidence for any of these modes and place 90% confidence level upper limits on their branching fractions in the range (1.5-26)×10−7.